A comparative study of risk factors for pancreatic fistula after pancreatoduodenectomy or distal pancreatectomy. Issue 8 (August 2017) - Halle-Smith, James M.; Vinuela, Eduardo; Brown, Rachel M.; Hodson, James; Zia, Zergham; Bramhall, Simon R.; Marudanayagam, Ravi; Sutcliffe, Robert P.; Mirza, Darius F.; Muiesan, Paolo; Isaac, John; Roberts, Keith J.
Abstract: Background: Evidence associates various biometric and histological variables such as steatosis and absence of fibrosis as risk factors for post-operative pancreatic fistula (POPF) after pancreatoduodenectomy (PD). Following distal pancreatectomy (DP), the association between these factors and POPF is less clear. This study of patients, drawn from the same background population, undergoing PD or DP at a single centre is a comparative study of the risk factors for POPF after these two operations. Methods: Associations between POPF and patient characteristics, pre-operative blood tests, data from pre-operative computed tomography (CT) imaging, assessment of histological steatosis and fibrosis were explored. Results: 26/107 (24%) and 26/90 (29%) patients developed POPF after PD and DP respectively. Absence of fibrosis was associated with POPF (p < 0.001) after PD and its presence correlated with pancreatic duct width (p < 0.001). Steatosis was not associated with POPF (p = 0.910). Multivariable analysis showed pancreatic duct width (p = 0.016) and fibrosis (p = 0.025) to be independent predictors of POPF after PD. The only variable associated with POPF after DP was underlying pathology (p = 0.005). Conclusion: Pancreatic duct width is the most important variable related to POPF after PD and is correlated with fibrosis. Steatosis was not related to POPF. In contrast, after DP POPF appears to be related to the underlying disease.